Comment l’écriture avec le numérique renouvelle la question du sujet adolescent : vers une géographie de l’écriture - Elisabeth Schneider (Recherches en Éducation)
The social, individual and cultural youth’s life, all the activities, are indeniably related to digital tools. Writing is always present because it’s a transversal technique- places, activities, supports, materials- which affords to question the adolescent subject. The theorycal tools of geography, information sciences and ethnography are involved in making sense of the youth’s use. A two years’ survey with teenagers in highschool, at home, in transport, and boardingschool, leads to analyse teens’ writing in a new way. We’ll examine the interest to think by cases to really see what the youth do when they write in the different contexts, across the media. Finally we try to see what a geography of writing could be.